2014
DOI: 10.15171/ijhpm.2014.52
|View full text |Cite
|
Sign up to set email alerts
|

Core attributes of stewardship; foundation of sound health system

Abstract: Stewardship is not a new concept for public policy, but has not been used to its optimum by the health policy-makers. Although it is being practiced in most successful models of health system, but the onus to this function is still due till date. Lately, few experts in World Health Organization (WHO) have realized its importance and have been raising the issue at different platforms to pursue the most important function of the health system i.e. stewardship. The core attributes of stewardship need to be unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…2 The WHO European Region also articulated the importance of health system functions in its Tallinn Charter. 3 While a number of studies on health systems functions have been conducted, the stewardship function has received limited attention to date, and is poorly understood 4,5 despite its centrality to health system performance. …”
Section: Introductionmentioning
confidence: 99%
“…2 The WHO European Region also articulated the importance of health system functions in its Tallinn Charter. 3 While a number of studies on health systems functions have been conducted, the stewardship function has received limited attention to date, and is poorly understood 4,5 despite its centrality to health system performance. …”
Section: Introductionmentioning
confidence: 99%
“…Stewardship has been defined as “the careful and responsible management of the well-being of the population,” and in the most general terms as “the very essence of good government.” Function of stewardship mainly relates to establishing and managing appropriate health information system, steering role of policy makers, program managers, leadership, and governance to make sound decisions. [1112] The resource generation function of WHO framework points out that to perform efficiently health systems requires the combination of many properly balanced physical and technical resource inputs. [1314] The service delivery function of the WHO framework refers to the combination of inputs into a production process that takes place in a particular organizational setting and that leads to the delivery of a series of interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 12 out of the 17 respondents considered the use of broad‐spectrum antibiotics justified, rational, and a cornerstone of ‘empirical therapy’. 40 A survey in a tertiary hospital in Karachi further reinforces the lack of stewardship, with 47% of the 200 medical doctors surveyed admitting they overprescribed antibiotics, either due to a lack of confidence in their diagnostic ability or as an acquiescence to patient demand. 41 The biggest blow to the principle of stewardship comes from the pharma‐physician nexus that has been reported in Pakistan.…”
Section: The Causes Of Abr In Pakistanmentioning
confidence: 99%
“…However, a study assessing the status of antibiotic stewardship in three major tertiary care hospitals in Pakistan found that whereas all 17 doctors surveyed agreed that ABR was a major problem, only those who had practiced in large private hospitals were familiar with the concept of stewardship. Furthermore, 12 out of the 17 respondents considered the use of broad‐spectrum antibiotics justified, rational, and a cornerstone of ‘empirical therapy’ 40 . A survey in a tertiary hospital in Karachi further reinforces the lack of stewardship, with 47% of the 200 medical doctors surveyed admitting they overprescribed antibiotics, either due to a lack of confidence in their diagnostic ability or as an acquiescence to patient demand 41 .…”
Section: The Causes Of Abr In Pakistanmentioning
confidence: 99%